Efek Kadar Urea Nitrogen Darah (BUN) pada Tikus Putih (Rattus norvegicus) Bunting Setelah Pemberian Monosodium Glutamat (MSG) Organik dan Sintetis - Tias, Eriza Putri Ayu Ning; Restiadi, Tjuk Imam; Widjiati, Widjiati; Wicaksono, M Galih; Setyaningsih, Endang (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to explores blood urea nitrogen (BUN) levels in Wistar rats exposed to synthetic and organic MSG to identify potential renoprotective effects. The study design involved a control group (K) that was fed a normal diet only, and six treatment groups (P1–P6) that received doses of organic or synthetic MSG at 60, 120, or 240 mg/kg BW for 19 days. Each group consisted of six rats. MSG was administered orally and BUN levels were measured using the colorimetric method. The results showed no significant difference in BUN levels between the control group and the treatment groups (p > 0.05). The highest BUN levels were found in the control group, while the lowest levels were found in the group that received the highest dose of synthetic MSG (240 mg/kg BW). Additionally, BUN levels were lower with organic MSG at 120 and 240 mg/kg BW than with the 60 mg/kg BW dose, suggesting that bioactive compounds in tempeh and pineapple bromelain may have renoprotective effects. While the lowest BUN levels were observed in the group receiving the highest dose of synthetic MSG (240 mg/kg BW), this may be due to reduced protein intake or other metabolic adaptations rather than safety factors. Synthetic MSG at a dose of 240 mg/kg BW produced the lowest BUN levels, which may indicate reduced protein intake or other metabolic adaptations, rather than safety factors.